Vigabatrin vs Carbamazepine in Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The efficacy and tolerability of vigabatrin (VGB) and carbamazepine (CBZ) monotherapy were compared in an open long-term study in newly diagnosed partial seizures in children treated at the Infantile Neuropsychiatric Division of the Regional Pediatric Hospital, Ancona, Italy.